Analisis Pengaruh Faktor Pemeliharaan terhadap Produktivitas Tanaman Kakao (Theobroma cacao L.) di Kabupaten Soppeng - Nur Hikma Arsyad; Junaedi Junaedi; Darmawan Darmawan; Rahmad; Syahruni Thamrin (Jurnal Agro Industri Perkebunan, 2026)
Cocoa is a strategic and economically valuable agricultural commodity in South Sulawesi Province, particularly in Soppeng Regency. However, cocoa productivity in the region remains relatively low and is declining, which is believed to be linked to suboptimal implementation of crop management practices. Furthermore, studies on the impact of management factors on cocoa productivity at the farmer level remain limited. This study aims to analyze the simultaneous and partial effects of maintenance factors on cocoa productivity in Soppeng Regency. The study was conducted from November 2025 to January 2026 in the Marioriwawo Subdistrict of Soppeng Regency. This study employed a quantitative, survey-based approach. The sample consisted of 110 productive cocoa farmers selected through snowball sampling based on specific criteria. Data collection was conducted via questionnaires, field observations, and interviews. Data analysis utilized descriptive analysis and multiple linear regression. The results indicate that all maintenance factors collectively significantly influence cocoa plant productivity. Pest and disease control partially influenced cocoa plant productivity (ρ < 0.01). Pruning and sanitation were significant at the 10% significance level but not at the 5% level. Meanwhile, fertilization and fertilizer application rates did not have a statistically significant effect on cocoa productivity. These results indicate that improving the effectiveness and consistency of maintenance practices, particularly in pest and disease control, is a key factor in increasing cocoa productivity.